BARRU DISTRICT GOVERNMENT POLICY CONCERNING THE PROHIBITION OF MODERN SHOPS - Nur Wafdatul Haeriyah,; Darussalam, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to find out what the Barru Regency government's policy is regarding the prohibition of modern shops. The main problem is divided into several sub-problems, namely: What is the policy of banning modern shops by the Barru Regency government, what are the factors causing the birth of the policy of banning modern shops by the Barru Regency government, and what is the impact on society of the policy of banning modern shops by the Barru Regency government. This type of research is classified as Descriptive Qualitative Field Research or Field Research. This research approach uses a Normative Sharia approach and an empirical approach, as well as data collection methods using observation, interviews and documentation. The research results in the research are that the Barru Regency Regional Government's policy regarding the prohibition on the establishment of Modern Shops is not to grant permits or limit permits for the establishment of modern shops in Barru Regency which can disrupt the growth of the local economy. The factors causing the ban on modern shops in Barru Regency are based on several factors, namely maintaining local economy, increasing MSMEs, and maintaining the balance of small traders, and the impact caused by the ban on modern shops has a positive impact, namely increasing local MSME businesses and a negative impact on the development of innovation and investment in Barru Regency as well as limited consumer choices.